Communication on reproductive health education for students with intellectual disability - Trie Damayanti, Yanti Setianti, Hanny Hafiar, Aat Ruchiat Nugraha, (Opción, 2019)
The purpose of this paper is to describe the communication activities of reproductive health education by teachers to students with intellectual disabilities. This research uses descriptive case study methods with qualitative data collection through interviews and observations. As a result, adolescents with intellectual disability have lower knowledge and negative attitudes towards reproductive health, thus requiring a specific approach and communication techniques. In conclusion, communication of reproductive health education for students with intellectual disabilities consists of the background of providing reproductive health information by teachers to adolescents with intellectual disabilities.